Creating a Basic Financial Plan for a Newly Graduated Naval Officers - Thianboonsong, Thawatchai (Journal of Applied Economics and Management Strategy, 2024)
The objective of this academic article is to provide a basic financial planning guide for newly graduated naval officers from the Naval Academy in Thailand. It aims to equip these naval officers with knowledge and understanding of the meaning and significance of financial planning, allowing them to adapt and apply this knowledge according to their specific needs and circumstances. Naval officers who graduate from naval school will receive a starting monthly salary of no less than 15,000 baht. As they receive higher salaries and gain more independence in decision-making compared to their time as naval cadets, it is highly essential for these naval officers to have financial knowledge related to financial planning and apply it for their benefit. Establishing financial planning guidelines should start with having basic financial knowledge and understanding the benefits of financial planning, clarifying why we are doing it. In the fundamental principles of financial planning, it is essential to create a personal budget and cash flow statement to assess your overall financial well-being. Starting with setting financial goals using the SMART framework (S = Specific, M = Measurable, A = Achievable, R = Realistic, T = Time-bound) is an effective way to establish financial objectives. Afterward, we can create a basic financial plan to evaluate our net worth and develop a simple cash flow statement to understand our income and expenses. Also, by understanding the use of Government pension fund and defined benefit plan from the government as one of the investment vehicles, we can predict a rough outcome as a result. A good financial plan enables us to achieve our life goals. Each individual’s financial plan may vary based on their circumstances and personal situations, but the underlying principles of financial planning remain consistent or similar in their application.